Editorial - Pacheco Romero, José (2015)
Our first lines are to greet the new executive management of the Peruvian Society of Obstetrics and Gynecology, led Dra. Rosario Gutierrez Pantoja, Gynecologist restless and very committed to the future of the specialty and we wish him every success in your Presidency . His first steps were to approach the members of the Company, through written, cards and details, and culminating this quarter with the cordial and friendly celebration of the OB, in which memories he gave gynecologists belonging to the Company for 50 years. In this case, rum was honored Drs. Hair Ascenzo Jorge Horacio Tregear and Juan Súccar. On the other hand, in addition to the fortnightly scientific activities, it is actively continuing the project to reduce maternal deaths in Piura, project sponsored by the International Federation of Gynecologists and Obstetricians.